Adult Education Attendance and Postsecondary Outcomes - Thomas Kouwe; David C. Ribar; Daphne Greenberg; Yiwei Duan (Institute of Labor Economics (IZA), 2023)
This paper analyzes postsecondary enrollment and academic outcomes for people who attended adult education classes in Georgia between July 2017 and December 2020, using linked administrative records for students in the state's adult education, technical college, and university systems. The paper estimates discrete-time hazard models of the time from when people start attending adult education classes until they enroll in a Georgia public postsecondary institution. The models consistently indicate that the probability of enrolling in a public postsecondary institution increases with the hours of adult education attendance and assessed skills. The paper also estimates regression models which show that the credit hours and grades adult learners earn in their first postsecondary enrollment terms increase with their previous hours of adult education class attendance.
Keywords: I23; J24; 330; adult basic skills education; demand for schooling; human capital; administrative data; event-history modeling